Elevated Resistin Levels are Associated with Inflammation in Hemodialysis Patients with Failed Renal Allografts. Issue 5 (May 2014) - Akagun, Tulin; Caliskan, Yasar; Yazici, Halil; Ozkok, Abdullah; Telci, Aysegul; Turkmen, Aydin; Yildiz, Alaattin; Sever, Mehmet Sukru
Background: Resistin is an adipocytokine, associated with insulin resistance and inflammation. The aim of this study is to evaluate the levels of serum resistin levels and other markers of inflammation in hemodialysis (HD) patients with failed renal allografts. Methods: Sixty-nine HD patients with failed renal allografts and 98 never transplanted (naive) HD patients and also 21 healthy controls were included in the study. Serum levels of various biochemical parameters as well as resistin, IL-6, TNF-α and hs-CRP as biochemical markers of inflammation, were measured. Results: Serum resistin levels in patients with failed renal allografts (4.80 ± 2.06 ng/mL) were significantly higher than those of the naive HD patients (3.44 ± 1.48 ng/mL) and healthy controls (0.95 ± 0.38 ng/mL; p<0.001). Patients with failed transplants were also characterized by higher TNF-alpha levels (96.8 ± 131.3 pg/mL vs. 40.9 ± 25.4 pg/mL; p<0.001) and IL-6 levels (83.9 ± 150.9 pg/mL vs. 14.6 ± 14.4 pg/mL; p<0.001) as compared to naive HD patients. Serum hs-CRP levels in patients with failed renal allografts (9.33 ± 11.86 mg/L) were significantly higher than those of the naive HD patients (1.26 ± 1.71 mg/L) and healthy controls (2.12 ± 1.82 mg/L; p<0.001). Serum albumin levels in patients with failed transplants (3.84 ± 0.47 g/dL) were lower as compared to never transplanted HD patients (4.13 ± 0.33 g/dL) and healthy controls (4.53 ± 0.40 g/dL; p<0.001). There was a positive correlation between serum resistin and TNF-alpha levels (r = 0.486, p<0.001). Conclusions: Serum resistin levels are increased in HD patients with failed renal allografts very probably reflecting an allograft-induced chronic inflammatory state.